2019
DOI: 10.1002/tesj.446
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation of meaning by mixed‐proficiency dyads in face‐to‐face and synchronous computer‐mediated communication

Abstract: Few studies have compared the nature of negotiation of meaning across face‐to‐face (FTF) and synchronous computer‐mediated communication (SCMC) modes with mixed‐proficiency dyads. Such comparisons can help identify important strengths and weaknesses of each mode. Therefore, this study explored whether FTF and SCMC modes differ in terms of frequency and quality of negotiations of meaning in English as a foreign language (EFL) learners’ interaction in mixed‐proficiency dyads. To this end, 32 EFL learners at elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…From the interactive, convergent, mixed-methods design, where quantitative and qualitative data were gathered concurrently (Creswell and Creswell 2018 ), we found that the students’ success in the course did not differ by modality of attendance. These findings are discrepant from the findings of Rovai and Jordan ( 2004 ) and Inglis et al ( 2011 ) but align with the findings of Fishman et al ( 2013 ), Liu and Rodriguez ( 2019 ), Moradi and Farvardin ( 2019 ), and Siczek and Stanchevici ( 2019 ). Our course proved to be an equalizer, as the post-test scores no longer differed by modality.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…From the interactive, convergent, mixed-methods design, where quantitative and qualitative data were gathered concurrently (Creswell and Creswell 2018 ), we found that the students’ success in the course did not differ by modality of attendance. These findings are discrepant from the findings of Rovai and Jordan ( 2004 ) and Inglis et al ( 2011 ) but align with the findings of Fishman et al ( 2013 ), Liu and Rodriguez ( 2019 ), Moradi and Farvardin ( 2019 ), and Siczek and Stanchevici ( 2019 ). Our course proved to be an equalizer, as the post-test scores no longer differed by modality.…”
Section: Discussioncontrasting
confidence: 53%
“…In a study of nonnative-English-speaking students, no significant differences in learning outcomes were yielded in terms of the frequency of negotiations of meaning (Moradi and Farvardin 2019 ). Although the study was conducted on English learners rather than their teachers, it is still relevant to the present context because language learning (as well as teaching) builds skills through frequent pair and small-group interaction, over a period of time as well as require formative feedback from the instructor.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, the FTF group showed some improvements revealing the fact that FTF instruction in settings with no technological tools can make some changes. In a similar line, Moradi and Farvardin (2019) reported no significant differences between the frequency of negotiations in face to face and synchronous modes. However, the results were controversial regarding the quality of negotiations.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, Stein et al (2007) argued that, with the appropriate teaching and social presence, students can arrive at a shared understanding in a synchronous environment. However, Moradi and Farvardin (2019) reported no significant differences between the frequency of negotiations in face to face and synchronous modes. But the results were controversial regarding the quality of negotiations because the SCMC mode requires L2 learners to type their messages, teachers can make benefit of these data by providing CF to learners after the chat to enhance their L2 learning.…”
Section: Synchronous Communicationmentioning
confidence: 90%